The impact of the difference of jurists on the verses of rulings contained in Surat Al-Kahf, the issues of the orphan as a model - Hammadi , Ahmed; Mohamed, Abdel Atallah (Islamic Sciences Journal, 2023)
Praise be to Allah, and prayers and peace be upon our master Muhammad, the Messenger of Allah , and his family and companions and those who follow him, and after: This research aims to explain the impact of the difference of jurists, may Allah Almighty have mercy on them, in the verses of rulings contained in Surat Al-Kahf, the issues of the orphan as a model, and the interpretation of the verses of rulings is characterized by that it contains Benefits in various sciences, as it includes the sciences of the Qur’an, the science of jurisprudence and its origins, the science of education and behavior, and the general meanings of the Qur’anic verses. And comment and weighting as required by the place. And that Surat Al-Kahf included many jurisprudential rulings, which the jurists derived from its noble verses, and among these are the issues and rulings of the orphan. And some provisions contained in the Holy Surah.